Neighbourhood-scale urban riparian ecosystem classification. (January 2017) - Wu, Meng; Che, Yue; Lv, Yongpeng; Yang, Kai
Highlights: A framework is required for urban riparian ecosystem classification. Indicators of biophysical landscape, built environment and human population can be used to stratify and classify urban riparian ecosystems. Neighbourhood-scale urban riparian ecosystem classification can guide the ecological compensation between different reaches of river. Riparian vegetation connectivity were negatively related to land use mix, built density and economic wealth. Abstract: Urban riparian ecosystems are now recognized as essential components in determining the vulnerability of nature and human systems to climate change, but still remains uncertainty concerning how to stratify and classify urban riparian landscapes into units of ecological significance at spatial scales appropriate for management. Ecosystem classification presents a tool that allows for quantifying the social and ecological processes of ecosystems so as to shape them into relatively homogeneous management objectives, and provides the potential of offering decision support to urban planners based on urban ecological principles. The purpose of this study is to explore and develop a framework for urban riparian ecosystem classification. The classification framework integrates 9 ecosystem components and 29 spatially-explicit variables that characterized by the biophysical landscape, built environment and human population. Then this framework is applied at the neighbourhood scale in Huangpu River basin, Shanghai city, China, employing hierarchical cluster analysis. The results of the ecosystem classification show that the riparian ecosystems in the Huangpu River could be grouped into three principal categories and these ecosystems are aligned along a gradient of increasing urbanization. We highlight the conservation and payment for riparian ecosystem services delivered in the upstream of Huangpu River, and revegetation and enhancement of riparian ecosystems in the more urbanized downstream area. We also find that riparian vegetation connectivity and coverage were negatively related to land use mix, built environment density, and economic wealth. In terms of riparian vegetation ecology, neighbourhood scale land use mix and built environment density are more influential than socioeconomic background (such as average family income and immigrant status).